2014
DOI: 10.3109/13506129.2014.937857
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid with macrophage migration correlates with augmented β-cell deficits in type 2 diabetic patients

Abstract: AimsIslet amyloid is a hallmark in type 2 diabetic subjects, but its implication in clinical features and development of islet pathology is still unclear.MethodsFrom 118 autopsy cases with type 2 diabetes, 26 cases with islet amyloid deposition (DA+) were selected. Twenty diabetic subjects without obvious amyloid deposition (DA−) matched for the age and diabetes duration and 20 non-diabetic subjects (ND) served for comparison. We examined the severity of amyloid deposition and its relationships with population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 43 publications
4
82
0
Order By: Relevance
“…A pancreatic morphometric analysis was performed as described (20,21). Pancreas tissue was dissected, weighed, and embedded into two paraffin blocks.…”
Section: Generation Of Sgpp2mentioning
confidence: 99%
“…A pancreatic morphometric analysis was performed as described (20,21). Pancreas tissue was dissected, weighed, and embedded into two paraffin blocks.…”
Section: Generation Of Sgpp2mentioning
confidence: 99%
“…There have also been conflicting results regarding the possible deleterious actions of islet-infiltrating macrophages. In fact, it has been reported that islets with invading macrophages are characterised by decreased insulin immunoreactivity, increased amyloid deposits, beta cells with oxidative stress-related DNA damage and reduced expression of the gene encoding proinsulin [8,24]. However, type 2 diabetic islets with increased CD68 + cells did not display an increased number of TUNEL + cells, and macrophages were not observed in the vicinity of apoptotic beta cells [8].…”
Section: Heterogeneity and Functional Role Of Islet Macrophages In Tymentioning
confidence: 88%
“…By using antibodies against CD68 (a likely marker of M1 macrophages) and CD163 (a likely marker of M2 macrophages), one study reported that intraislet-infiltrating macrophages were both CD68 + and CD163 + [8]; however, in a different article it was shown that whereas the number of islet-associated CD68 + macrophages in type 2 diabetic Martino et al (2015) Increased infiltration and invasiveness Macrophage infiltration also in the non-endocrine pancreas [10] amyloid-positive islets was increased, that of CD163 + cells was not [24]. There have also been conflicting results regarding the possible deleterious actions of islet-infiltrating macrophages.…”
Section: Heterogeneity and Functional Role Of Islet Macrophages In Tymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, de Koning and colleagues found that macrophage density was not different between islets with and without amyloid in diabetic humans and Macaca mulatta monkeys, nor between hIAPP transgenic and control mice (de Koning et al 1998). In a more recent study, amyloid-positive islets in T2D were found to have significantly more macrophages (CD68+ cells) accumulating within or near amyloid plaques and around microvessels relative to matched T2D subjects without amyloid and to non-diabetic controls (Kamata et al 2014). The majority of CD68+ cells in this study co-expressed nitric oxide synthase 2 (NOS2), whereas the number of …”
Section: Iapp Aggregates Induce Islet Inflammationmentioning
confidence: 92%